Developing an at‐home dementia rehabilitation intervention: An iterative qualitative codesign study - Clare Stephenson; Sophia Hadjimichael; Kasia Bail; Diane Gibson; Stephen Isbel; Michelle Bennett; Nathan M. D'Cunha (Australian Occupational Therapy Journal, 2026)
Abstract Introduction There is limited availability of community‐based rehabilitation for people with dementia. This study explored stakeholder perspectives to inform the design of an occupational therapy‐led at‐home dementia rehabilitation programme. Methods Four co‐design workshops were conducted over 6 months with 16 participants, including people with dementia, care partners and health‐care professionals. Transcribed workshop discussions underwent iterative thematic analysis to inform the final intervention components and philosophical foundations. Consumer and Community Involvement People with dementia and their care partners discussed what an at‐home dementia rehabilitation programme should entail. As consumer and community contributors, they informed programme refinements by shaping decisions about intervention content at each workshop. Findings Four themes underpinned the intervention components and philosophical foundations for the programme: (1) accessible dementia care, driven by increased community awareness; (2) person‐centred care: understanding a person's unique needs, preferences and goals; (3) empowerment through community engagement and continuous support; and (4) coordinated multidisciplinary care, essential for continuity and effectiveness. Person‐centred care requires tailoring individual goals within a multidisciplinary structure, with allied health assistant intervention delivery and personalised resources prepared with oversight from the occupational therapist. Stakeholders endorsed programme leadership by occupational therapists, with physiotherapy support where mobility or exercise components were required and delivery by allied health assistants under clinical supervision. Conclusion Codesign workshops defined an at‐home dementia rehabilitation intervention founded on occupational therapy philosophies of care, with accessibility, empowerment and a comprehensive referral and intake process as central to individualisation. Assessing the programme's feasibility and effectiveness may enable personalised care that helps people with dementia maintain independence at home. Allied health assistants may offer a cost‐effective option, improving access to rehabilitation for people with dementia, as with other chronic conditions.